2000
DOI: 10.1021/ac000780u
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Detection of Dysplastic Tissue by Raman Spectroscopy

Abstract: The detection of dysplasia and early cancer is important because of the improved survival rates associated with early treatment of cancer. Raman spectroscopy is sensitive to the changes in molecular composition and molecular conformation that occur in tissue during carcinogenesis, and recent developments in fiber-optic probe technology enable its application as an in vivo technique. In this study, the potential of Raman spectroscopy for in vivo classification of normal and dysplastic tissue was investigated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
120
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(121 citation statements)
references
References 27 publications
1
120
0
Order By: Relevance
“…In the past decade, optical spectroscopic methods such as Raman spectroscopy have been comprehensively investigated for cancer and precancer diagnosis and evaluation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Raman spectroscopy measures inelastic light scattering and is a vibrational spectroscopic technique that can provide specific spectroscopic fingerprints based on the molecular composition and structures of biological tissues (3,4,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, optical spectroscopic methods such as Raman spectroscopy have been comprehensively investigated for cancer and precancer diagnosis and evaluation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Raman spectroscopy measures inelastic light scattering and is a vibrational spectroscopic technique that can provide specific spectroscopic fingerprints based on the molecular composition and structures of biological tissues (3,4,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Less water absorption makes it easy to detect other tissue components and results in deeper light penetration into the tissue. As such, NIR Raman spectroscopy has received great interest for in vivo and in vitro diagnosis of malignancies in a number of organs including the colon (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). NIR Raman spectroscopy studies showed that tissue Raman spectral features could be used to correlate with the molecular and structural changes associated with neoplastic transformations (5,7,10,12), demonstrating the feasibility of NIR Raman spectroscopy technique for early cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…9 -12 The accurate detection of BCC has attracted much attention from clinical dermatologists since it is difficult to distinguish BCC tissue from surrounding noncancerous tissue. [13][14][15][16] The routine diagnostic technique used for the detection of BCC is pathological examination of biopsy samples. This involves removal of tissue from suspected areas, which is then sliced and stained to enable the pathologist to identify morphological abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Initial work in rats models in-vitro showed potential for in vivo applications. 74 Safety and feasibility of using Raman probes in the oesophagus was shown using an Enviva Visionex probe. 400 spectra in 20 patients were measured using 5 second acquisition times, although discrimination of pathology was poor 67 due to large sampling depths.…”
Section: Endoscopic Diagnostic Applicationsmentioning
confidence: 99%